The Effect of Teaching English Language Subject Based On (Yes, No, Po) Strategy In Achievement And Motivation Towards Learning It For Tenth Grade Female Students - Hammad, Safaa Ismail; Aljadiri, Adnan Hussein (Journal of Curriculum and Teaching Methodology, 2022)
The study aimed to identify the effect of teaching English Language based on (Yes, No, Po) strategy in achievement and motivation towards learning English for tenth grade female students. A quasi-experimental design of two unequal groups design was used. The study sample consisted of (60) female students from the tenth grade of primary School in Um Qaseer and Al-Muqabaleen Mixed Secondary Schools in Amman Capital. The sample distributed into two sections. The first sample was taught by the (Yes, No, Po) strategy, and the number of students was (31), the second as a control group (29) female students who was taught by traditional method. Two measurements were developed, first: the achievement test, which consisted of (25) multiple choice questions, and Second: the measure of motivation towards learning English Language consisted of (28) items. And the two instruments were verifyied according to their psychometric properties. The results appealed that there was a statistical significant difference at the level of significance (α = 0.05) in the achievement of the tenth grade students in English in favor of the experimental group. Also, there was a statistical significant difference at the level of significance (α = 0.05) in the motivation towards learning English in favor of the experimental group. Finally, the study recommended to develop guides and training programs for English Language teachers to introduce them to the importance of using (Yes, No, Po) strategy and urge them to implement the strategy.